Characterization of UV-cured gel polymer electrolytes for rechargeable lithium batteries - Song, MK; Cho, JY; Cho, BW; Rhee, HW (ELSEVIER, 2002)
Novel ultraviolet (UV)-cured gel polymer electrolytes based on polyethyleneglycol diacrylate (PEGDA) oligomer and polyvinylidene fluoride (PVdF) are prepared and characterized. UV curing of PEGDA oligomer containing PVdF and ethylene carbonate (EC)-based liquid electrolyte yields chemically and physically cross-linked PEGDA/PVdF blend gel electrolytes. PEGDA/PVdF blend films show much higher mechanical properties and electrolyte liquid retention than pure PEGDA film. The ionic conductivity (sigma) of a PEGDA/PVdF (5/5) blend electrolyte reaches about 4 mS cm(-1) at ambient temperature and is as high as 1 mS cm(-1) I at 0 degreesC. All the blend electrolytes are electrochemically stable up to 4.6 V versus Li/Li+. The cation transference number (t(+)) measured by do micropolarization exceeds 0.5 at room temperature. Li/(PEGDA/PVdF)/LiCoO2 cells (2 cm x 2 cm) retains >91% of its initial discharge capacity after 50 cycles at the C/3 rate (2 mA cm(-2)) and delivers about 70% of full capacity with an average load voltage of 3.6 Vat the C/1 rate. Cell performance is stable up to 80 degreesC because PVdF chains might be stabilized by entanglement with the chemically cross-linked PEGDA network structure. (C) 2002 Elsevier Science B.V All rights reserved.